Modern Art for a Modern China: The Chinese Intellectual Debate 1900 – 1930 - LEI YANG (Journal of Dharma, 2025)
Yiyan Wang’s Modern Art for a Modern China: The Chinese Intellectual Debate 1900–1930 offers an interdisciplinary account of how art reform became integral to China’s cultural, political and educational transformation in the early twentieth century. Focusing on debates among artists, poets, writers, critics and educators, Wang shows how Chinese intellectuals integrated art reform and aesthetic movements with broader initiatives of modernization, nationalism and cosmopolitanism. The book highlights pivotal figures such as Cai Yuanpei, Lu Xun and Xu Zhimo, emphasizing their contributions to aesthetic education, art institutions, exhibitions, international cultural exchange and the relationship between modern Chinese literature and visual art. It also challenges Western historiographies that understate Chinese agency under semi-colonial conditions, foregrounding intellectual self-fashioning and cultural regeneration.